Métodos para identificação de moléculas com atividade herbicida com ênfase na rota de síntese de carotenóides - Corniani, Natália [UNESP] (2013)
Weed management has always been an important aspect of crop production. The introduction of synthetic herbicides in the mid-20th century has made weed control less expensive and more effective. The introduction of transgenic crops resistant to non-selective synthetic herbicides (e.g., glyphosate and glufosinate) further established the reliance on herbicides as the dominant technology used for large-scale weed control in production agriculture worldwide. However, the selection pressure imposed by herbicides has led to the widespread evolution of herbicide resistance in weed populations, which is a major threat to the sustainability and profitability of cropping systems. Reliable tests for resistance are an essential pre-requisite for the rational implementation of effective integrated control strategies. There is increasing demand from growers to test for weed resistance and learn how to manage it. Scientists have developed resistance-testing protocols for numerous herbicides but, in Brazil, there is no review compiling this information. Evolution of herbicide resistance is also underscoring the need for herbicides with new modes of action to complement those herbicides failing due to resistance. The 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway represents one of the most promising targets to develop new herbicides as well as targets to improve the nutritional value of crop plants. However, there is just one commercial herbicide, clomazone, targeting it. Therefore, in the first chapter of this study there is a compilation of assays to measure the activity of key target enzymes and characterization of plant resistance to all known herbicides mode of action. Since no in vivo assay was available for testing inhibitors of MEP pathway, in the second chapter it is described the development of a rapid, accurate, cheap, readily available leaf disc assay based on the measurement of the carbon ...